A política de EJA EPT no CTISM: um estudo sobre as transformações vivenciadas na e para além da pandemia - Winter, Shirley Bernardes (2021)
The present work, "The EPT EJA policy in CTISM: a study on the transformations experienced in and beyond the pandemic", composes the dissertation of the Academic Master's Degree in Vocational and Technological Education of the Industrial Technical College of the Federal University of Santa Maria (CTISM-UFSM). It is linked to the research line LP1: Policies and Management in Vocational and Technological Education, within the research groups TransformAção - Study and Research Group on Public Policies and Pedagogical Workin Vocational Education and Kairós - Study and Research Group on Work, Education and Public Policies. The research sought to analyze the transformations experienced by student workers accessing the EJA EPT policy in CTISM in the period 2019-2021 and by teacher workers in this context and beyond. In order to achieve this goal, specific objectives were defined, namely: contextualize the historicity of the EJA EPT policy in Brazil and in CTISM; monitor the relations of education and work of the workers-students of the EJA EPT Electromechanics course in the period 2019-2021; report the transformations of the workers- students of the Electromechanics course in the period 2019-2021, in relation to the challenges of access, permanence success, including the experience of the Covid-19 pandemic; problematize the pedagogical work and the necessary transformations in the experience of the pandemic. The qualitative and dialectical study had as research subjects the student-workers and the teacher- workers of the EJA EPT of CTISM. The search for an answer to the research problem happened through the use of bibliographic and documental data production techniquesand those resulting from the field research, in which online questionnaires were used for students and teachers, records in a field diary, dialogue groups with students from the three classes and teachers who participated in the research, in order to redefine the data produced. Toanalyze the data, we used the categories of the dialectical method (historicity, totality, contradiction, and praxis) imbricated in the content categories (work, students, teachers,pedagogical work, pandemic, success, and transformations). The results of this study point out that the transformations observed by the students were more in the professional sense, which reaffirms what we have been defending since the beginning of this research, of the great influence that the world of work has on the lives of these subjects. The changes observed by the teachers in relation to the students, on the other hand, were mostly personal. Therefore, in the space-time of the research there were many transformations, whether in the world of work, in education, or in the experience of the pandemic that required teachers and students to transform themselves to continue promoting/accessing knowledge. We also observed that the researched reality has constituted itself as an institution that promotes the access, permanence, and success of students through a pedagogical work engaged with the policy of the right to youth and adult education integrated to Professional Education.